Aspectos da participação política e da atuação de entidades assistenciais num município de pequeno porte do interior paulista: o caso de Urupês - Crivelaro, Sérgio Henrique Rezende (Universidade Federal de São Carlos, 2007)
This work aims to understand the organization of the political dimension of the small municipalities before the ideals of democracy and sustainability for public policy and planning. It starts with the hypothesis that the political dimension of the small municipalities is configured by 1) closer relations of sociability (such as mutual understanding, personality, friendship, neighborhood, kinship), 2) institutions of public character (on religious and assistance), 3) and the municipal administration itself (mainly represented by the figure of the mayor). The research strategy is based on the exploratory case study unique. As empirical object was selected Urupês municipality located in the northwestern region of São Paulo, Brazil. Through literature review, exploratory survey, direct observation, interviews, questionnaires and systematization of the data, the results confirm the hypothesis proposed and allow the following considerations: 1) the characteristics of sociability are important and provide channels of communication, participation and social representation to identify the demand and provision of public character, aggravating or benefiting the social and environmental conditions in the city, 2) lack a greater understanding of the role of each actor in society, 3) lack most effective communication not only formal between executive, legislative and judicial branches, 4) entities of public nature, especially of a religious and care nature, play an important role with regard to minimizing social inequalities. Thus, the characterization of the political dimension of the small municipalities proved to be very relevant to clarify possibilities and minimize contradictions for thinking about public policies for sustainable and democratic planning.
Aspects of political participation and performance of charities in a small city in São Paulo State, Brazil: the case of Urupês
Keywords: Sustentabilidade democrática; Municípios de pequeno porte; Políticas públicas; Políticas públicas e planejamento; Democratic sustainability; Politics dimension; Small cities; Public politics and planning; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL